HUBUNGAN TEKNIK MENYUSUI DENGAN PROSES INVOLUSI UTERUS PADA IBU POST PARTUM FISIOLOGIS 0-14 HARI DI TPMB “S” CILINCING - Hidayati, Nurul; Siswati, Eny; Masyayih, Warda Anil; Novia, Deti (LPPM STIKES HUSADA JOMBANG, 2025)
Background: Uterine involution or uterine contraction is a process in which the uterus returns to its pre-pregnancy state. Uterine involution can also be said to be the process of returning the uterus to its original state or pre-pregnancy state. Objectives: The purpose of the study was to analyze the relationship between breastfeeding techniques and the process of uterine involution in post-partum physiological mothers 0-14 days at TPMB